2023
DOI: 10.3390/app13063732
|View full text |Cite
|
Sign up to set email alerts
|

Functional Electrostimulation in Patients Affected by the Most Frequent Central Motor Neuron Disorders—A Scoping Review

Abstract: Post-stroke sequelae, spinal cord injury and multiple sclerosis are the most common and disabling diseases of upper motor neurons. These diseases cause functional limitations and prevent patients from performing activities of daily living. This review aims to identify the potential of functional electrical stimulation (FES) for locomotor rehabilitation and daily use in upper motor neuron diseases. A systematic search was conducted. For the search strategy, MeSH terms such as “stroke”, “functional electrical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…Therefore, improving walking ability is a main objective for rehabilitation. Various studies carried out for the rehabilitation of patients with central motor neuron disease have shown that classic rehabilitation programs based on physical therapy [5] and physiotherapy can have very good results on spasticity [6] and Appl. Sci.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improving walking ability is a main objective for rehabilitation. Various studies carried out for the rehabilitation of patients with central motor neuron disease have shown that classic rehabilitation programs based on physical therapy [5] and physiotherapy can have very good results on spasticity [6] and Appl. Sci.…”
Section: Introductionmentioning
confidence: 99%